MEMBANGUN KARAKTER SISWA MELALUI LITERASI DIGITAL DALAM MENGHADAPI PENDIDIKAN ABAD 21 (REVOLUSI INDUSTRI 4.0) - Khasanah, Uswatun; Herina, Herina (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The development of the world at this time has changed the era of industrial revolution 4.0, human life forms have shaped information. Therefore, in preparation that is supported and able to compete globally, as well as regulating the development of technology is very important for all people and for the future of the nation and state. Therefore digital literacy needs to be developed in the world of education today to build a better national character and be better prepared for the 21st century education era. This article aims to learn how to build the character of students as students from elementary school to digital secondary school through Digital Literacy (Digital-Age Literacy) in learning for education with 21st Century education. Education with this literal digital dimension can develop digital literacy learning materials and methods in schools and outside schools, in relation to the 21st century education era (Industrial Revolution 4.0). This study uses a Qualitative Descriptive method with a scientific background, the aim of which is to describe the phenomena that occur in the current environment, data obtained through observation, interviews and documentation.